(untitled) (The Review of Diabetic Studies, 2024)
Sepsis is a clinical emergency arising from a dysregulated host response to infection, and remains among the leading causes of preventable death worldwide, demanding rapid and integrated diagnostic strategies. The progression of sepsis to septic shock can occur within hours, causing irreversible organ dysfunction if immediate interventions are not implemented. In modern critical care and emergency medicine, the implementation of point-of-care (POC) biomarkers—including lactate, procalcitonin (PCT), C-reactive protein (CRP), presepsin, and cytokine panels—has markedly enhanced clinicians’ ability to detect tissue hypoperfusion and bacterial infection earlier than traditional central laboratory methods. At the same time, nursing-driven clinical assessment remains fundamental for early recognition because bedside clinicians continuously monitor physiological deterioration often before biochemical abnormalities are detected. This review critically evaluates the diagnostic accuracy and response time efficiency of POC biomarkers compared to structured nursing assessment models such as NEWS2, MEWS, and qSOFA. The integration of real-time bedside assessment with rapid diagnostic platforms strengthens the early sepsis recognition chain, minimizes delays in antibiotic administration, and supports national quality improvement agendas — including Saudi Vision 2030 — aimed at reducing sepsis mortality through digital transformation, workforce empowerment, and standardized early detection pathways.